2016
DOI: 10.12659/msm.896961
|View full text |Cite
|
Sign up to set email alerts
|

7, 8, 3’-Trihydroxyflavone Promotes Neurite Outgrowth and Protects Against Bupivacaine-Induced Neurotoxicity in Mouse Dorsal Root Ganglion Neurons

Abstract: Background7, 8, 3′-trihydroxyflavone (THF) is a novel pro-neuronal small molecule that acts as a TrkB agonist. In this study, we examined the effect of THF on promoting neuronal growth and protecting anesthetics-induced neurotoxicity in dorsal root ganglion (DRG) neurons in vitro.Material/MethodsNeonatal mouse DRG neurons were cultured in vitro and treated with various concentrations of THF. The effect of THF on neuronal growth was investigated by neurite outgrowth assay and Western blot. In addition, the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Since we expected THF to at least match the effect of BDNF, the lack of any effect from the THF treatment is surprising. More so since recently, in in vitro studies in mice and rats, THF has been found to be effective in promoting neurite outgrowth in dorsal root ganglion explants [57] and cochlear SGC explants [47] in a reportedly TrkB-dependent manner. Frick et al [47] compared the effects of BDNF with THF on neurite outgrowth.…”
Section: The Elusive Effect Of Thfmentioning
confidence: 99%
“…Since we expected THF to at least match the effect of BDNF, the lack of any effect from the THF treatment is surprising. More so since recently, in in vitro studies in mice and rats, THF has been found to be effective in promoting neurite outgrowth in dorsal root ganglion explants [57] and cochlear SGC explants [47] in a reportedly TrkB-dependent manner. Frick et al [47] compared the effects of BDNF with THF on neurite outgrowth.…”
Section: The Elusive Effect Of Thfmentioning
confidence: 99%
“…General anaesthetics are divided into inhaled and intravenous types; they mainly inhibit cerebral cortical activity, which are represented by propofol and N 2 O 5 . However, animal studies have found that almost all clinically used intravenous anaesthetics can result in neurodegenerative and abnormal synapses during critical periods of brain development, leading to late behavioural changes and cognitive dysfunction 6,7 . Furthermore, the anaesthetics, including propofol, have been proven to induce the apoptosis of nerve cells whilst exerting its benefits, especially in paediatric surgery, which can cause irreversible damage to developmental neurons 8 .…”
Section: Introductionmentioning
confidence: 99%
“…5 However, animal studies have found that almost all clinically used intravenous anaesthetics can result in neurodegenerative and abnormal synapses during critical periods of brain development, leading to late behavioural changes and cognitive dysfunction. 6,7 Furthermore, the anaesthetics, including propofol, have been proven to induce the apoptosis of nerve cells whilst exerting its benefits, especially in paediatric surgery, which can cause irreversible damage to developmental neurons. 8 Therefore, studying the side effects of anaesthetics and exploring the underlying mechanisms will be helpful for improving the safety of anaesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal DRGn are afferent neurons of peripheral nervous system and primary neurons of sensory conduction system. With the increasing research on the nervous system, such as the pain mechanism of diseases [1][2][3], spinal cord injury repair [4,5], electrophysiological research [6][7][8][9], it is necessary to establish a simple and easy-to-obtain primary nerve cell culture scheme.…”
Section: Introductionmentioning
confidence: 99%